B-cell tolerance. - Ferry, H; Leung, J; Lewis, G; Nijnik, A; Silver, K; Lambe, T; Cornall, R (2006)
Autoreactive B cells are actively tolerized to more abundant self-antigens by a series of checkpoints involving receptor editing, deletion, anergy and competition for growth factors. In contrast, B cells reactive against rare, sequestered or tissue specific self-antigens remain functionally naïve. During an immune response, the autoimmune danger from these cells is countered by a variety of mechanisms comprising control of self-antigen presentation, limitation of immunogenic and tolerogenic costimuli including T cell help, homeostatic control of growth and strict regulation of germinal centre reactions. In this overview we consider how knowledge of these checkpoints may be used to gain a better understanding of transplant tolerance and the generation of alloantibodies.